High Five Strategy to Improve Students’ Reading Comprehension - Susi Purnama Sari (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2019)
This article aimed to know the improvement of students’ reading comprehension of narrative text after using High Five strategies and common factors influenced the changes of students’ reading comprehension of narrative text by using High Five strategies at XI IPA 2 of Senior High School 1 Merangin Jambi. The result showed that in two cycles to answer these research questions: first, the students’ mean score improved 22,44 point or 26%; second, these improvements were influenced by students’ reading interest and motivation, materials selection, and reading strategies. In conclusion, this research showed that the use of High Five Strategy could improve students’ reading comprehension of narrative text at XI IPA 2 of Senior High School 1 Merangin Jambi. Keywords: High Five Strategy, Reading Comprehension, Factors in Students’ Reading Comprehension